MAKNA TERORISME DALAM FILM ALIF LAM MIM - Windi Pradini; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Terrorism is a term for terrorist group, while terror is an intentinally act done by a group intentionally that aims to influence, intimidate people in order to feel insecure and uncomfortable also to make other people feel scared so that it can attract people’s attention, group or nation. Like the terrorism depicted in the film Alif Lam Mim by which terrorism is portrayed as clothed in the ways of the muslims wearing the robe and the turban over the head, also terrorists who are always identified with violence.This study uses descriptive qualitative method which is analyze by Roland Barthes semiotics model, data collection techniques has been used observation of audio/dialogue and visual display in the film Alif Lam Mim, documentation, and interview by using purposive sampling technique.The result of research show that there is a meaning of terrorism in the film Alif Lam Mim namely that a Kyai who is considered as the leader of terrorist, and the clothes of the moeslims are suspected as terrorists and it becomes society perception or that it is a terrorist outfit, as well as the actions of a colonel to the muslims issues about Islam to the public to get an the higher position and make a bad image of religion in the point of view society.Keywords:Film, Terrorism, Alif Lam Mim, Moeslem